Analisis Penggunaan Fly Ash Tipe F pada Beton Non Pasir sebagai Green Concrete - Purnamasari, Eka; Antonius; Setiyawan, Prabowo (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
The use of concrete as a construction material has become an industry standard; however, excessive exploitation of natural sand has had a negative impact on the environment. No-fines concrete has emerged as an innovative alternative to reduce dependence on sand, offering advantages such as a porous structure that enhances permeability and thermal insulation. This study analyzes the use of Type F Fly Ash, a byproduct of coal combustion from the Asam-Asam Power Plant in South Kalimantan, as an additive in no-fines concrete to improve its mechanical properties and durability. Fly Ash acts as a pozzolanic material, which can partially replace cement and enhance compressive strength and resistance to extreme environmental conditions. The research was conducted through a literature review and cement and Fly Ash testing. The results indicate that the increase in Fly Ash content affects the cement hydration reaction, necessitating the selection of an appropriate dosage tailored to specific construction project needs. The incorporation of Type F Fly Ash enhances ecological sustainability and concrete efficiency, while simultaneously reducing industrial waste and the environmental impact of cement production. Therefore, no-fines concrete based on Fly Ash presents a sustainable solution for environmentally friendly infrastructure development.